2006
DOI: 10.3354/ame044105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ChangJiang River summer discharge on bottom-up control of coastal bacterial growth

Abstract: The East China Sea (ECS) has one of the largest shelf ecosystems in the world, and among the major external forces that affect physical and biogeochemical processes over the ECS shelf is discharge from the ChangJiang (CJ) River. This is particularly true during summer when prevailing flooding leads to the annual maxima of CJ River discharge. To explore the effects of interannual variations in CJ River summer discharge on bacterial growth rate (BGR), 6 cruises were conducted over the entire width of the ECS she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…N : G ratios were exceptionally low in the northern basin (0.07 to 0.1) where the Sakawa River discharged. Shiah et al (2006) found that bacterial growth rate increases with increase in river discharge from the Chang-Jiang River to the East China Sea. The low ratios in the northern basin could thus be due to enhanced bacterial respiration associated with freshwater discharge.…”
Section: Resultsmentioning
confidence: 99%
“…N : G ratios were exceptionally low in the northern basin (0.07 to 0.1) where the Sakawa River discharged. Shiah et al (2006) found that bacterial growth rate increases with increase in river discharge from the Chang-Jiang River to the East China Sea. The low ratios in the northern basin could thus be due to enhanced bacterial respiration associated with freshwater discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our understanding of global carbon cycling in the coastal oceans depends on our knowledge of how large river discharges influence ecological processes in the adjacent sea. One such large river system, on which there is limited information, is the Changjiang River, which discharges into the East China Sea (ECS) [e.g., Gong et al , 2006; Shiah et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is worth noting that direct relationships between bacterial growth and river flow may be explained by different causal mechanisms: a bacterial growth stimulation by riverine DOM, by phytoplankton-derived DOM, or both (see Figure 6). The former explanation probably applies to the East China Sea ecosystem (see Figure 6(b); Shiah et al, 2006).…”
Section: Hydrologic Control Of Bacterial Resources and Growth Ratesmentioning
confidence: 98%
“…Episodic meteorological events (e.g., wind storms and high rainflow episodes), for example, stimulate heterotrophic bacterioplankton due to increased availability of organic matter and/or inorganic nutrients associated to increased con tinental runoff or benthic resuspension (Cotner et al, 2000;Grémare et al, 2003;Alonso-Saéz et al, 2008;Solic et al, 2009). Variability in river discharge rates, usually considered a proxy for organic carbon flux into estuarine systems (Jassby et al, 1993), is also positively related to bacterial production and growth over seasonal (Murrell et al, 1999;Schultz et al, 2003) and interannual time scales (Murrell, 2003;Shiah et al, 2006;Barrera-Alba et al, 2009). In some estuaries, a shift in ecosystem metabolism toward heterotrophic dominance is observed under increased freshwater discharge rates (see Hitchock et al, 2010).…”
Section: Hydrologic Control Of Bacterial Resources and Growth Ratesmentioning
confidence: 99%
See 1 more Smart Citation